From Theory to Practice: Empirical Insights on BPM Lifecycle Adoption and Low-Code Utilization in SMEs - Pavel Arno (IEEE Access)
Small and medium-sized enterprises (SMEs) face growing pressure to adapt to dynamic, competitive markets. Business Process Management (BPM) offers a strategic pathway to operational efficiency and digital transformation. While the BPM lifecycle and low-code platforms are frequently presented as key enablers for SMEs, few empirical studies examine their practical implementation. This study addresses two research questions: 1) how SMEs use low-code technologies to support BPM, and 2) how they apply – or deviate from – the traditional BPM lifecycle. Using a triangulated research design combining a rapid literature review and an expert survey of BPM practitioners in SMEs, the study finds that low-code tools are widely adopted for basic BPM tasks such as process modeling and workflow automation. However, advanced features like AI and process mining are underutilized. Likewise, SMEs often skip or adapt BPM lifecycle phases due to organizational constraints. These findings highlight a gap between BPM theory and SME practice, emphasizing the need for more adaptive BPM frameworks and accessible low-code solutions tailored to SME contexts.